(untitled) (Derna Academy Journal for Applied Sciences, 2025)
Septicemia and bacterial meningitis remain life-threatening conditions, particularly among newborns and critically ill patients with weakened immunity. The widespread misuse of antibiotics has further complicated diagnosis by contributing to antimicrobial resistance. Rapid, reliable, and cost-effective diagnostic markers are therefore urgently needed. This study aimed to evaluate the diagnostic role of C-reactive protein (CRP) and white blood cell (WBC) count in detecting septicemia and bacterial meningitis. A descriptive-analytical, hospital-based design were conducted at Misurata Medical Center, Libya, between January 2023 and May 2024. After ethical approval, data were obtained from the Medical Laboratories Department, including blood cultures, cerebrospinal fluid (CSF) cultures, CRP levels, and WBC counts. A total of 274 patients were enrolled (34% male, 66% female; age range: 1 day–71 years). Pathogens isolated from CSF included Staphylococcus aureus (7 cases), Streptococcus spp. (1), and Acinetobacter spp. (1). Blood cultures yielded S. aureus (5), Streptococcus spp. (3), Acinetobacter spp. (3), Klebsiella spp. (2), and single isolates of Bacillus spp., Enterococcus spp., and Candida albicans. Correlation analysis showed significant associations between positive blood cultures, elevated CRP, and increased WBC counts, while no significant correlation was found with CSF cultures. The most effective antibiotics identified were amikacin (AK), ciprofloxacin (CIP), gentamicin (CN), ceftriaxone (CRO), piperacillin/tazobactam (TZP), and imipenem (IMP).